An investigation into psychological stress and its determinants in Xinjiang desert oil workers. Issue 15 (April 2018) - Ning, Li; Guan, Suzhen; Liu, Jiwen
Abstract : Abstract: The present study aims to investigate psychological stress and its determinants in Xinjiang field oil workers. Specifically, we aim to elucidate the mechanisms underlying psychological stress by comprehensively and quantitatively evaluating the processes involved in psychological stress, the factors which influence it, and their relationship. The participants were 1200 field oil workers in Xinjiang who had been in service for at least 1 year. A structural equation model based on data from the symptom checklist, social support research scale, personality questionnaire, occupational burnout questionnaire, and occupational stress questionnaire was constructed to investigate the social (environmental) factors that influence physiological stress and the interplay among these factors. The positive incidence of psychological stress in the field oil workers in Xinjiang was 12.54%. The structural equation model indicated that the main factors that influenced psychological stress in these workers included social support (0.077), occupational role (0.165), personal strain response (0.139), personality (0.189), and occupational burnout (0.380). Among these factors, occupational role, personality, and occupational burnout had a relatively strong predictive power for psychological stress reactions. The cortisol level in workers with positive psychological stress was significantly higher than that in workers with negative psychological stress. Occupational stress, personality, and occupational burnout exert an impact on psychological stress in field oil workers. Therefore, interventions to address these factors should be taken to reduce the incidence of psychological stress.